Millennial Clients' Trust-Building Strategies In Mental Health Counseling - Siti Rahayu Pratami Lexianingrum; Uud Wahyudin; Susanne Dida; Iis Latifah Nuryanto (Ma'soem University, 2025)
Trust is a key element in the effectiveness of the mental health counseling process, especially in reaching millennials who have unique characteristics in terms of values, communication, and expectations of psychological services. This study aims to identify and analyze effective strategies counselors use in building trust with millennial clients. Using a descriptive qualitative approach, data was obtained through in-depth interviews and observations with professional counselors who are experienced in working with clients aged 20-35. The results revealed four main strategies used consistently, namely: (1) empathic and authentic communication, (2) the use of storytelling and personal narratives, (3) the application of inclusive and culturally sensitive language, and (4) the use of digital media as an initial medium for building trust. The findings confirm the importance of cultural competence and adaptation of counseling approaches to the social and technological dynamics faced by the millennial generation. Practical implications of this research include the need for more contextualized counselor training, as well as the development of service policies that accommodate relational and digital approaches in modern counseling practices.